2014
DOI: 10.1186/s12866-014-0254-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glycoproteins secreted by wild-type Botrytis cinerea and by protein O-mannosyltransferase mutants

Abstract: BackgroundBotrytis cinerea secretes a high number of proteins that are predicted to have numerous O-glycosylation sites, frequently grouped in highly O-glycosylated regions, and analysis of mutants affected in O-glycosylation has shown, in B. cinerea and in other phytopathogenic fungi, that this process is important for fungal biology and virulence.ResultsWe report here the purification of glycoproteins from the culture medium, for a wild-type strain of B. cinerea and for three mutants affected in the first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 56 publications
(83 reference statements)
2
33
0
Order By: Relevance
“…BcSUN1 (Bcin06g06040.1, from the B. cinerea protein database in EnsemblFungi 1 ; van Kan et al, 2016) is a highly glycosylated protein of 48 kDa, initially identified as a component of the B. cinerea early secretome (Espino et al, 2010) and also present in the glycosecretome (González et al, 2014). The alignment of its sequence with the four S. cerevisiae proteins that belong to Group-I of the SUN family (Supplementary Figure S2) showed an overall identity ranging from 28.1% for NCA3 to 38.6% for SIM1 ( Table 1 ), while sequence conservation was higher for the C -terminal region containing the SUN domain, with amino acid sequence identities ranging from 41 to 46%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…BcSUN1 (Bcin06g06040.1, from the B. cinerea protein database in EnsemblFungi 1 ; van Kan et al, 2016) is a highly glycosylated protein of 48 kDa, initially identified as a component of the B. cinerea early secretome (Espino et al, 2010) and also present in the glycosecretome (González et al, 2014). The alignment of its sequence with the four S. cerevisiae proteins that belong to Group-I of the SUN family (Supplementary Figure S2) showed an overall identity ranging from 28.1% for NCA3 to 38.6% for SIM1 ( Table 1 ), while sequence conservation was higher for the C -terminal region containing the SUN domain, with amino acid sequence identities ranging from 41 to 46%.…”
Section: Resultsmentioning
confidence: 99%
“…Botrytis cinerea strains used in this work were B05.10 (Quidde et al, 1999), a wild type strain, and B05.10-BcSUN1, which expresses a tagged version of the BcSUN1 protein under the control of the OliC promoter (González et al, 2014). These were kept as conidial suspensions in 15% glycerol at -80°C for long storage, and were maintained on 3% malt extract agar (MEA, Oxoid, UK) plates for routine use.…”
Section: Materials and Methdosmentioning
confidence: 99%
See 3 more Smart Citations